The role of foreign investors and local agents in the derivatives market and their impact on the exchange rate in Colombia: A wavelet analysis - Fredy Gamboa-Estrada (Graduate Institute of International and Development Studies, 2023)
Changes in net positions of foreign and local investors in the forward market may have differential effects on the spot exchange rate. This paper assesses the role of different sectors in the derivatives market and their potential impact with other fundamentals on the spot exchange rate in Colombia. Using wavelet band spectrum regressions, I find that changes of net forward positions of foreign investors impact the exchange rate at short terms scales. There is evidence that the real sector has a significant and permanent effect on the spot exchange rate at different frequencies that is higher in the long term. Other fundamentals such as the interest rate differential, CDS, and oil prices affect the exchange rate at lower frequencies, which is consistent with the exchange rate determination puzzle. This approach differs substantially from traditional regression methods such as ordinary least squares (OLS) which are not suitable to identify the relationship between variables at different frequencies over time.
Keywords: C1; C22; C58; F31; G11; 330; Foreign investors; local investors; exchange rate; wavelet analysis; band spectrum regression